Exploration of (Non)Entrepreneurial Intent: A Narrative Inquiry Examining Exogenous Elements - Hamal, Sanjay (Social Inquiry: Journal of Social Science Research, 2019)
I began this paper with an inquisitiveness to understand the post-studies intention of undergraduate students. My research focuses on the after studies intent of students: job, business/entrepreneurship or something else. I do not propose any essence for 'why or why not' of entrepreneurship/business or job. Thus, this article is a product from a large data set that I had gathered for my Masters of Philosophy (MPhil) dissertation. In this article, I aim to explore my participants' intention towards entrepreneurship through their narratives. To explore and analyse their stories, I examine exogenous elements in shaping their entrepreneurial intent. In exploring the entrepreneurial intent of my participants, I take refuge of 'intention model' proposed by Krueger (1993) and look into exogenous factors such as 'perceived social norms', 'perceived desirability' and 'perceived self-efficacy', 'personal feasibility' to form (non)entrepreneurial intent. Through understanding my participants’ life-stories, however, I come to the conclusion that non/entrepreneurial intent are a result of interacting situational and socio-cultural factors.